The Removal of Zinc, Chromium and Nickel from Industerial Waste-Water Using Banana Peels - Al-Azzawi, M.; Shartooh, S.; Al-Hiyaly, S. (Iraqi Journal of Science, 2023)
The current study was designed for using banana peels to remove zinc, chromium and nickel from industrial waste-water. Three forms of these peels (fresh, dried small pieces and powder) were tested under some environmental factors such as pH, temperature and contact time. Current data show that banana peels are capable of removing zinc, chromium and nickel ions at significant capacity. Furthermore, the powder of banana peels had highest capability in removing all zinc, chromium and nickel ions followed by fresh peels whilst dried peels had the lowest bioremoving capacity again for all metals under test. The highest capacity was for chromium then nickel and finally zinc. All these data were significantly (LSD peel forms = 2.761 mg/l, LSD metal ions = 1.756 mg/l) varied. In case of chromium, these figures were 65.0 ± 1.0 mg/l, 54.0 ± 2.0 mg/l and 41.7 ± 1.5 mg/l for powder, fresh and dried peels respectively. Regarding nickel ions, these data were 56.7 ± 1.5 mg/l for peel powder, 47.7 ± 2.2 mg/l for fresh peel and 47.7 ± 2.2 mg/l for dry peel. While for zinc ions, the biosorption capacity was 51.7 ± 0.8 mg/l, 41.0 ± 1.0 mg/l and 34.7 ± 0.9 mg/l for powder, fresh and dry peels respectively. However, some examined factors were found to have significant impacts upon bioremoval capacity of banana peels such as pH, temperature, and contact time where best biosorption capacity was found at pH 4, at temperature 50 Cº and contact time of 1 hour. It is true that banana peels were varied significantly in case of metal ions and increasing examined factor (pH, temperature. And contact time). Regarding pH, the highest bioremoval ability was found at pH 5 for all heavy metals, but with the sequence of Cr, Ni, and Zn and the data were 59.4 ± 0.83 mg/l, 54.0 ± 0.0 mg/l and 39.1 ± 1.86 mg/l respectively. Similar pattern of bioremoval capacity was detected for temperature which was 50 C º where it was 66.7 ± 2.91 mg/l for chromium, 57.7 ± 1.12 mg/l for nickel and 52.0 ± 1.12 mg/l for zinc. However, in case of contact time, the capacity of biosorbing of these metals was again similar to those of pH and temperature factors where it was found to be 74.0 ± 1.76 mg/l , 66.0 ± 2.25 mg/l and 66.0 ± 1.95 mg/l for Cr, Ni, and Zn respectively but at 1 hour contact time.